Determinants of Capital Structure for Malaysian Shariah-Compliant Firms: The Impact of Revised Screening Methodology - Rahim, Norfhadzilahwati; Mat Nor, Fauzias; Ramli, Nurainna; Marzuki, Ainulashikin (UUM Press, 2019)
This study investigates two main objectives. Firstly, the determinants of capital structure were examined for each sector among Malaysian Shariah-compliant firms, and whether the inclusion of Islamic debt (leverage 1 and leverage 2) has led to different results due to changes in the screening methodology. Secondly, this paper analyzes the target Capital Structure and Speed of Adjustment for both before and after the Revised Screening Methodology. This study employs panel data analysis by using generalized method of moment (GMM). The sample consists of 192 Shariah-compliant companies in Malaysia during the period of 1999 to 2017. The results demonstrated that the firm has target capital structure and identified specific determinants that have affected the capital structure of Shariah-compliant firms in Malaysia. Moreover, the findings have also revealed certain implications toward large firms. Large firms tend to generate more income and profit, however at the same time, these firms require more debt to support investment activities. Hence, with regards to profitability, this study identified a negative relationship between profitability and leverage for Shariah-compliant firms for all sectors. Shariah-compliant firms with high profitability will use a lower leverage in their financial activities. Thus, the results strongly support the pecking order theory. Other than that, this study found that the lagged dependent variable (lagged leverage 1 and leverage 2) presented a positive significance and concluded that the speed of adjustment takes approximately 2 years. This suggests that the Shariah-compliant firms close approximately by 30% to 70% of the gap between current and target capital structure within one and two years. Furthermore, the findings on the target leverage level imply that after the revised screening methodology was introduced in November 2013, the speed of adjustment became faster than before the implementation of the new screening methodology. Thus, it is important for management to maintain the target leverage during financial decision making, which in turn strengthens the firms Shariah-compliant financial stability and sustainability and continue to remain listed as Shariah-compliant securities. This paper provides an overview of capital structure behaviour in Malaysia.